Phosphatidylinositol 3-Kinase-Associated Protein (PI3KAP)/XB130 Crosslinks Actin Filaments through Its Actin Binding and Multimerization Properties In Vitro and Enhances Endocytosis in HEK293 Cells - Yamanaka, Daisuke; Akama, Takeshi; Chida, Kazuhiro; Minami, Shiro; Ito, Koichi; Hakuno, Fumihiko; Takahashi, Shin-Ichiro (Frontiers in Endocrinology, 2016)
Actin-crosslinking proteins control actin filament networks and bundles and contribute to various cellular functions including regulation of cell migration, cell morphology and endocytosis. Phosphatidylinositol 3-kinase-associated protein (PI3KAP)/XB130 has been reported to be localized to actin filaments (F-actin) and required for cell migration in thyroid carcinoma cells. Here we show a role for PI3KAP/XB130 as an actin-crosslinking protein. First, we found that the carboxyl terminal region of PI3KAP/XB130 containing amino acid residues 830-840 was required and sufficient for localization to F-actin in NIH3T3 cells and this region directly bound to F-actin in vitro. Moreover, actin crosslinking assay revealed that recombinant PI3KAP/XB130 crosslinked F-actin. In general, actin-crosslinking proteins often multimerize to assemble multiple actin-binding sites. We then investigated whether PI3KAP/XB130 could form a multimer. Blue native (BN)-PAGE analysis showed that recombinant PI3KAP/XB130 was detected at 250 kDa-1200 kDa although the molecular mass was approximately 125 kDa, suggesting that PI3KAP/XB130 formed multimers. Furthermore, we found that the amino terminal 40 amino acids were required for this multimerization by co-immunoprecipitation assay in HEK293T cells. Deletion mutants of PI3KAP/XB130 lacking the actin-binding region or the multimerizing region did not crosslink actin filaments, indicating that actin binding and multimerization of PI3KAP/XB130 were necessary to crosslink F-actin. Finally, we examined roles of PI3KAP/XB130 on endocytosis, an actin-related biological process. Overexpression of PI3KAP/XB130 enhanced dextran uptake in human embryonic kidney (HEK) 293 cells. However, most of the cells transfected with the deletion mutant lacking the actin-binding region incorporated dextran to a similar extent as control cells. Taken together, these results demonstrate that PI3KAP/XB130 crosslinks F-actin through both its actin-binding region and multimerizing region and plays an important role in endocytosis.